2022
DOI: 10.25295/fsecon.1028730
|View full text |Cite
|
Sign up to set email alerts
|

Can Elon Mask's Twitter Posts About Cryptocurrencies Influence Cryptocurrency Markets by Creating a Herding Behavior Bias?

Abstract: The main purpose of this study is to examine the effects of Elon Mask's Twitter posts about cryptocurrencies on cryptocurrency markets within the scope of herding behavior bias. For this purpose, the daily price values and transaction volumes of Bitcoin and Dogecoin are analyzed by applying the EGARCH models. The results show that Elon Musk's positive Twitter posts increase dogecoin's volatility more than bitcoin in terms of price and trading volume. In addition, the effect of positive tweets has been found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…Aharon et al (2022) studied the impact of Twitter Uncertainty on four cryptocurrencies and concluded that any uncertainty discussed in social media effect the cryptocurrency returns. Hamurcu (2022) analyzes Elon Mask's Twitter posts on two cryptocurrencies, i.e. Bitcoin and Dogecoin, using the EGARCH model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aharon et al (2022) studied the impact of Twitter Uncertainty on four cryptocurrencies and concluded that any uncertainty discussed in social media effect the cryptocurrency returns. Hamurcu (2022) analyzes Elon Mask's Twitter posts on two cryptocurrencies, i.e. Bitcoin and Dogecoin, using the EGARCH model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, some influencers try to play the perception of the cryptocurrency market with pump signal efforts. This is in line with the findings Hamurcu (2022) that Elon Musk's positive tweet regarding the Dogecoin token was able to boost the price of Dogecoin. This confirms that the effect of personal postings made by influencers on social media is able to influence the Dogecoin market, so that the interest of buyers to buy the token is higher.…”
Section: Literature Reviewsupporting
confidence: 90%
“…En tal sentido, la gestión del riesgo de liquidez debe ser una prioridad en estos casos, debido a que una noticia convulsa en una latitud lejana puede causar un desplome inmediato del activo, dejando al inversionista a expensas del mercado que, si bien afecta al dinero tradicional, las fluctuaciones no resultan tan violentas como en los criptoactivos. De hecho, no es necesario que exista un suceso severo que afecte la cotización; es más, resulta hasta innecesario un hecho real, ya que basta con el tweet de una personalidad para que se registre un desplome, por ejemplo: el caso de la dependencia de Bitcoin con respecto a las declaraciones del empresario Elon Musk (Hamurcu, 2022).…”
Section: Riesgos Financieros En El Uso De Criptoactivosunclassified